2021
DOI: 10.21272/mmi.2021.2-02
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of intellectual property: innovative impact on global competitiveness of national economies

Abstract: This paper investigates the role of intellectual property in the modern post-industrial economy and its intensive commercialization of the country's competitive advantages in the global economic environment. The main purpose of the research is to prove the hypothesis about the crucial role of intellectual property development in ensuring expanded public reproduction and facilitating the global competitiveness of national economies through innovative modernization of production. To gain the research aim, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The issue of devising a strategy for the introduction of intelligent and innovative technologies into the economic circulation for enterprises in the field of industrial production requires a detailed analysis. Their consideration involves the study of technologies for internal and external transfer of innovations, creation of commercialization programs, and construction of innovative models for the prospective development of industrial production [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of devising a strategy for the introduction of intelligent and innovative technologies into the economic circulation for enterprises in the field of industrial production requires a detailed analysis. Their consideration involves the study of technologies for internal and external transfer of innovations, creation of commercialization programs, and construction of innovative models for the prospective development of industrial production [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Syhyda et al (2020) identified the relationship between innovation and Industry 4.0 as a basis for developing the Internet of Things and information transformation. The innovations in commercialization are well studied, particularly in terms of the innovative impact of intensive commercialization of the post-industrial economy on the country's competitive advantages in the global economic environment (Virchenko et al, 2021). Lyeonov et al (2020), Chukwu and Kasztelnik (2021), and Didenko and Sidelnyk (2021) analyze the innovative technologies introduced in the financial sector, which is inextricably linked with the functioning of the other national economy sectors and interdependent with the business environment parameters.…”
mentioning
confidence: 99%